Crashing Implementation in Construction Project Case - ARAP, ENES (İstanbul Kültür Üniversitesi, 2022)
Due to the diversity of decision-making alternatives, uncertainty, and cost of making errors, it has become more complex today than ever before, and decision-making has grown considerably more challenging in the construction sector and its atmosphere (Haque, 2010). As a result, relying on a trial-and-error strategy or an experimental decision has become extremely challenging or even a bad choice in decision-making. When dealing with construction projects, it is always necessary to complete the project within a given timeframe to keep expense costs as low as conceivable assuming the continually changing conditions in the construction field. Failure to do so increases the overall costs. Thus, there must be a time-cost trade-off. This study mainly provides a case study for reducing total project time to reach the completion objective at the least total cost. Two approaches are compared such as crashing the project with the Critical Path Method using the manual network diagraming approach and crashing the project by developing the mathematical model and solving it using Excel software. The manual crashing increased the project cost by almost 11.2% and decreased the project duration by 115 days which is more than 35% of the total duration. The optimum solution provided by the solver for the mathematical model, on the other hand, resulted in a lower cost increase of 9.7% in project costs with the same reduction in total project duration.
Bir İnşaat Projesinin Zaman-Maliyet Karşlaşma Analizi
▪ Yüksek lisans tezi.
Keywords: Project Management; Time-Cost Tradeoff; Project Crashing